VUV Photoionization and Ab initio determination of the ionization energy of a gas-phasesugar (deoxyribose) - Ghosh, Debashree; Golan, Amir; Takahashi, Lynelle K.; Krylov, Anna I.; Ahmed, Musahid (Journal of Physical, 2012)
The ionization energy of gas-phase deoxyribose was determined using tunable vacuum ultraviolet synchrotron radiation coupled to an effusive thermal source. Adiabatic and vertical ionization energies of the ground and first four excited states of alpha-pyranose, the structure that dominates in the gas phase, were calculated using high-level electronic structure methods. An appearance energy of 9.1(+/- 0.05) eV was recorded, which agrees reasonably well with a theoretical value of 8.8 eV for the adiabatic ionization energy. A clear picture of the dissociative photoionization dynamics of deoxyribose emerges from the fragmentation pattern recorded using mass spectrometry and from ab initio molecular dynamics calculations. The experimental threshold 9.4 (+/- 0.05) eV for neutral water elimination upon ionization is captured well in the calculations, and qualitative insights are provided by molecular orbital analysis and molecular dynamics snapshots along the reaction coordinate.